ANALISIS PERENCANAAN SUMBER DAYA MANUSIA DAN KINERJA ORGANISASI DI SEKTOR PEMERINTAH KOTA GUNUNGSITOLI - Pandu Laowo (Jurnal Performa)
Human Resource Planning (HRP) has gained a lot of attention as a method that connects the strategic goals of the organization with human resources programmes and policies. HRP Planning influences employee performance with empirical support individually, but overall HRP planning is strongly related to organization performance. The focus of this research is to explore the analysis of human resources planning on the performance of organizations in the government sector in gunungsitoli city. Using qualitative methods by gathering data through observations and literature studies. In this research use theory and concepts related to SDM planning, Organizational performance and government sector, as an analytical tool in understanding or describing research issues. The result of this research is that the SDM is basically one of the internal resources that, if well utilized, could potentially provide a competitive advantage to the organization in this regard within the City of Gungsitoli government organization. The SDM planning helps the City Government organization in determining whether they are equipped with the right human resources for the organization that are in line with the objective of improving the performance of the organisation in the public service. The City Government of Gungsitoli implemented the planning but not all aspects of the component - component of the SDM planning achieved or realized, so there are obstacles in targeting good organizational performance in the public service.